Imagining A Medieval English Nation - Lavezzo, Kathy (Book collections on Project MUSE., 2004)
Examining a diverse array of texts--ranging from Latin and vernacular historiography to Ricardian poetry and chivalric treatises--this volume reveals the variety of forms "England" assumed when it was imagined in the medieval West.